The effect of vitamin D supplementation on the muscle damage after eccentric exercise in young men: a randomized, control trial - W. Pilch; B. Kita; A. Piotrowska; Ł. Tota; M. Maciejczyk; O. Czerwińska-Ledwig; E. Sadowska- Krepa; S. Kita; T. Pałka (Taylor & Francis Group, 2020)
Background Vitamin D contributes to the optimal functioning of muscles. This study was designed to determine the modulating effect of vitamin D supplementation on the degree of muscle cell damage caused by eccentric exercise in young men. Methods 60 male volunteers (20-24 years old) taking part in this study were divided in two groups - with suboptimal (S) and optimal (O;) 25(OH)D plasma levels. These groups were randomly subdivided into groups with vitamin D supplementation (experimental: SE and OE) and controls (SC and OC). Before the supplementation (Test I) and after 3 months (Test II), participants were subjected to two rounds of eccentric exercise tests on a declined treadmill (running speed corresponded 60% VO2peak determined in each subject in incremental exercise test). During each test, blood samples used for determination of 25(OH)D, Il-1β, myoglobin (Mb) levels and CK, LDH activity were taken at three timepoints: before the test, 1 h and 24 h after it ended. After distribution normality testing (Saphiro-Wilk test), statistical analyses were performed. Non-parametric: Kruskal-Wallis test and the Wilcoxon test were applied, and the Dunn-Bonferroni test as a post-hoc test. Results In all groups, after 3 months, higher concentrations of 25(OH)D were indicated (SE p = 0.005; SC p = 0.018; OE p = 0.018; OC p = 0.028). SE and SC groups showed higher baseline concentrations of Il-1β and significantly higher concentrations of this interleukin after 1 h compared to groups with an optimal 25(OH)D level. After supplementation, the SE group reacted with a similar jump in concentration of Il-1β as the OC and OE groups. The change after 1 h after exercise in Test II was significantly different from that from Test I (p = 0.047) in SE group. Lower Mb concentrations indicated 1 h after exercise in Test II for SC and SE groups were indicated. CK activity did not differentiate the studied groups. Plasma calcium and phosphate disorders were also not indicated. Conclusions The study has shown that vitamin D doses determined from the plasma concentration of 25(OH)D of individuals to match their specific needs can significantly reduce muscle cell damage induced by eccentric exercise.